Religious Moderation in the Islamic Education System in Indonesia - Khasanah, Nur; Irwan Hamzani, Achmad; Aravik, Havis (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
This research aims to describe the concept of religious moderation, examine religious moderation in Islamic education, and examine models of religious moderation practice in Indonesia. This research uses a phenomenological approach. The type of research includes library research. The data used is secondary data sourced from documents. Data collection techniques were carried out through online searches. Next, the data was analyzed using an interactive analysis model. This research shows that religious moderation is a tolerant religious attitude. The main principle of moderation is finding a middle point characterized by tolerance. Religious moderation in Islamic education is the concept of moderate Islamic education, which places more emphasis on substantive teaching aspects. Islamic material puts forward teachings that bring benefits and soothe humanity. Teaching a moderate understanding of Islam in educational institutions is mandatory for all educational institutions. The practice model of religious moderation in Islamic education has been practiced in several institutions in Indonesia, both educational and non-educational institutions, through training. Some elements implemented are an inclusive curriculum, inter-religious dialogue, respect for diversity, and prevention of radicalism. Religious moderation is a religious attitude that respects differences. Religious moderation in Islamic education emphasizes substantive teachings. The practice model of religious moderation in Islamic education has been practiced in educational and non-educational institutions.